Two new species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Myanmar, and their phylogenetic relationships with related species in the S. asakoae species-group - Hiroyuki Takaoka (2018)
© 2017 Elsevier B.V. Two new species of Simulium (Gomphostilbia), S. (G.) myanmarense and S. (G.) monglaense, are described from females, males, pupae and larvae from Myanmar. The two new species are placed in the S. asakoae species-group, and are similar to each other in the female and male but distinguished in the pupa by the presence or absence of an anterodorsal projection of the cocoon, and in the larva by a unique pattern of colored markings on the abdomen. Taxonomic notes are given to separate these species from related species. The COI gene sequences of both species are compared with those of eight species of the S. asakoae species-group and three species of the S. ceylonicum species-group. Both new species are most closely related to each other, further supporting their morphological classification in the S. asakoae species-group.